Role of Serum Levels of Thymidine Kinase 1 in Diagnosis and Differentiating of Prostatic Tumor - Lara Balasim Al-Dahy; Basil O. Mohammed; Saad Dakhil F. Daraji; Mazin M. Farhan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Both benign prostatic (BPH) and prostate (Pca) hyperplasia include prostate enlargement. Thedistinction between benign prostatic hyperplasia and prostate cancer is a major challenge, since the prostaticspecific antigen (PSA) cannot be considered a reliable predictor of prostate cancer. Aims: Efficiency ofserum thymidine kinase 1 and PSA-related biomarkers in prostate tumor, BPH and PCa diagnosis anddifferentiation, especially when serum PSA is in the gray (4-10 ng/ml) region and in the pronostic of thesepatients after surgical therapy. Subjects and Methods: A case control and cross-sectional review. Therewere 110 elderly patients (45-81 years) and 45 controle. Serum experiments involved the use of ELISAtechnologies to measure tPSA, fPSA, and TK1. Result: In comparison to both of the BPH and controls, themean (±S D) of serum tPSA and fPSA in Pca were significantly improved (all p =0,001) while the meanvalue of f PCa in comparison with BPH and control was dramatically decreased (p = 0,001) for fPSA/tPSA.There was no difference between BPH and controls in these parameters. In both of the Pca and Controls(P<0.001) the mean TC1 was slightly higher (P<0.001). This serum TK1 has the most receptive and specificdiagnostic and differentiating potency in the gray zone of tPSA (4-10 ng/ml), which has tPSA in the grayzone with AUC=1 in the 924 pg/ml cut-off zone.Conclusion: Serum level of TK1 was superior of tPSA in diagnosis of prostate tumor and differentiatingbetween BPH and PCa.